(3ELGRI ef eMeO QAha GdZdGej GdfLej dYHO GdeLjO Hf ESeGYjd GdNWjHs - (3YHO GdeLjO Hf ESeGYjd GdNWjHs ((3eDjO Hf eMeO QAha GdZdGej s)
(3ChdgG (B:s
(3CMeO Gddg Ydi LRjd GdEMSGf hYXje GdefI s
(3BNQgG (B:s
(3hGf jJLfH GdQjGA hGdeQGA hGdLOGd , hdGjJgdc Ydi MH GdeGd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B15 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI Bd GdNWjH HGdehUd (B(3/20) s
Keywords: (3GdJGQjNs